Developing Ancermat (Anthology of Mathematics Story) Digital Learning Media to Improve Students’ Problem-Solving Ability - Nuhyal Ulia; Mohamad Hariyono; Imam Kusmaryono; Rida Fironika Kusumadewi (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThe use of digital-based learning media is very necessary for teachers.  The existing limited media becomes the main reason why Ancermat (anthology of mathematical stories) learning media is developed and expected to be able to improve elementary school students’ problem solving skills. This study aims to describe the stages of the development of Ancermat learning media and find out whether it meets valid, practical criteria, and its effectiveness. The method used was the development research. The data analysis comprised of validity test analysis, practicality test analysis, and analysis of Ancermat media effectiveness using descriptive statistics and gain normalization test. The results showed that Ancermat learning media met the valid score of 4.53 with very high criteria and fulfilled the practicality test based on the students’ responses reaching an average score of 4.41 with very good criteria. Based on the gain test, it reached 0.580 with moderate criteria and met the minimum criteria of mastery learning with t count = 27.33> t table = 2.042, meaning that the average score of the problem-solving skill tests met the minimum criteria of mastery learning. So, it can be concluded that the Ancermat learning media meets the criteria of being valid, practical, and effective in improving the mathematical problem solving abilities of elementary school students.Keywords: ancermat, learning media digital, problem solving skills, elementary school students. AbstrakPenggunaan media pembelajaran berbasis digital sangat diperlukan bagi para guru. Keterbatasan media yang ada menjadi alasan utama dikembangkannya media pembelajaran Ancermat (antologi cerita matematika) dan diharapkan dapat meningkatkan kemampuan pemecahan masalah siswa sekolah dasar. Penelitian ini bertujuan untuk mendeskripsikan tahapan pengembangan media pembelajaran Ancermat dan mengetahui apakah memenuhi kriteria valid, praktis, dan efektif. Metode yang digunakan adalah penelitian pengembangan. Analisis data meliputi analisis uji validitas, analisis uji kepraktisan, dan analisis efektivitas media Ancermat menggunakan statistik deskriptif dan uji normalisasi Gain. Hasil penelitian menunjukkan bahwa media pembelajaran Ancermat memenuhi skor valid sebesar 4,53 dengan kriteria sangat tinggi dan memenuhi uji kepraktisan berdasarkan respon siswa mencapai skor rata-rata 4,41 dengan kriteria sangat baik. Berdasarkan hasil uji n-gain mencapai 0,580 dengan kriteria sedang dan memenuhi kriteria ketuntasan minimal dengan t hitung = 27,33 > t tabel = 2,042, artinya skor rata-rata tes keterampilan pemecahan masalah matematika siswa memenuhi kriteria ketuntasan minimal. Sehingga dapat disimpulkan bahwa media pembelajaran Ancermat memenuhi kriteria valid, praktis, dan efektif meningkatkan kemampuan pemecahan masalah matematika siswa sekolah dasar.Kata kunci: ancermat, media pembelajaran digital, keterampilan pemecahan masalah, siswa sekolah dasar.